Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the equation
[tex]\[ \frac{k}{k+5} + \frac{5}{7-k} = 1 \][/tex]
we will walk through the process in a structured manner.
1. Combine the fractions on the left-hand side:
To do this, we need a common denominator. The common denominator for the fractions [tex]\(\frac{k}{k+5}\)[/tex] and [tex]\(\frac{5}{7-k}\)[/tex] is [tex]\((k+5)(7-k)\)[/tex].
[tex]\[ \frac{k}{k+5} + \frac{5}{7-k} = \frac{k(7-k) + 5(k+5)}{(k+5)(7-k)} \][/tex]
2. Expand and simplify the numerator:
[tex]\[ k(7-k) + 5(k+5) = 7k - k^2 + 5k + 25 = 12k - k^2 + 25 \][/tex]
So, the equation now looks like this:
[tex]\[ \frac{12k - k^2 + 25}{(k+5)(7-k)} = 1 \][/tex]
3. Eliminate the denominator by multiplying both sides by [tex]\((k+5)(7-k)\)[/tex]:
[tex]\[ 12k - k^2 + 25 = (k+5)(7-k) \][/tex]
4. Expand the right-hand side:
[tex]\[ (k+5)(7-k) = k \cdot 7 + k \cdot (-k) + 5 \cdot 7 + 5 \cdot (-k) = 7k - k^2 + 35 - 5k = 2k - k^2 + 35 \][/tex]
Thus, we have:
[tex]\[ 12k - k^2 + 25 = 2k - k^2 + 35 \][/tex]
5. Isolate the terms involving [tex]\(k\)[/tex] on one side:
[tex]\[ 12k - k^2 + 25 - 2k + k^2 - 35 = 0 \][/tex]
[tex]\[ 10k - 10 = 0 \][/tex]
[tex]\[ 10k = 10 \][/tex]
6. Solve for [tex]\(k\)[/tex]:
[tex]\[ k = \frac{10}{10} \][/tex]
[tex]\[ k = 1 \][/tex]
Therefore, the solution to the equation
[tex]\[ \frac{k}{k+5} + \frac{5}{7-k} = 1 \][/tex]
is [tex]\(\boxed{1}\)[/tex].
[tex]\[ \frac{k}{k+5} + \frac{5}{7-k} = 1 \][/tex]
we will walk through the process in a structured manner.
1. Combine the fractions on the left-hand side:
To do this, we need a common denominator. The common denominator for the fractions [tex]\(\frac{k}{k+5}\)[/tex] and [tex]\(\frac{5}{7-k}\)[/tex] is [tex]\((k+5)(7-k)\)[/tex].
[tex]\[ \frac{k}{k+5} + \frac{5}{7-k} = \frac{k(7-k) + 5(k+5)}{(k+5)(7-k)} \][/tex]
2. Expand and simplify the numerator:
[tex]\[ k(7-k) + 5(k+5) = 7k - k^2 + 5k + 25 = 12k - k^2 + 25 \][/tex]
So, the equation now looks like this:
[tex]\[ \frac{12k - k^2 + 25}{(k+5)(7-k)} = 1 \][/tex]
3. Eliminate the denominator by multiplying both sides by [tex]\((k+5)(7-k)\)[/tex]:
[tex]\[ 12k - k^2 + 25 = (k+5)(7-k) \][/tex]
4. Expand the right-hand side:
[tex]\[ (k+5)(7-k) = k \cdot 7 + k \cdot (-k) + 5 \cdot 7 + 5 \cdot (-k) = 7k - k^2 + 35 - 5k = 2k - k^2 + 35 \][/tex]
Thus, we have:
[tex]\[ 12k - k^2 + 25 = 2k - k^2 + 35 \][/tex]
5. Isolate the terms involving [tex]\(k\)[/tex] on one side:
[tex]\[ 12k - k^2 + 25 - 2k + k^2 - 35 = 0 \][/tex]
[tex]\[ 10k - 10 = 0 \][/tex]
[tex]\[ 10k = 10 \][/tex]
6. Solve for [tex]\(k\)[/tex]:
[tex]\[ k = \frac{10}{10} \][/tex]
[tex]\[ k = 1 \][/tex]
Therefore, the solution to the equation
[tex]\[ \frac{k}{k+5} + \frac{5}{7-k} = 1 \][/tex]
is [tex]\(\boxed{1}\)[/tex].
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.